Poor comparability of coagulation screening test with specific measurement in patients receiving direct oral anticoagulants: results from a multicenter/multiplatform study. (15th October 2016) - Testa, S.; Legnani, C.; Tripodi, A.; Paoletti, O.; Pengo, V.; Abbate, R.; Bassi, L.; Carraro, P.; Cini, M.; Paniccia, R.; Poli, D.; Palareti, G.
Abstract : Essentials Prothrombin and partial thromboplastin time (PT/PTT) measure direct oral anticoagulants (DOACs). PT, PTT and specific tests for DOACs were performed on patients treated for atrial fibrillation. Normal PT/PTT don't exclude DOAC activity and their prolongation doesn't confirm DOAC action. The use of PT or PTT to evaluate DOAC activity could cause dangerous misinterpretations. Summary: Background: Prothrombin time (PT) and activated partial thromboplastin time (APTT) have been proposed to measure the effect of oral anti‐activated factor X (FXa) or anti‐activated FII drugs, respectively. Aims: To evaluate the relationships and responsiveness of PT and APTT versus direct oral anticoagulant (DOAC) concentrations measured with specific coagulation tests performed with different platforms in four Italian anticoagulation clinics. Methods: Six hundred and thirty‐five patients with atrial fibrillation participated in the study: 240 were receiving dabigatran, 264 were receiving rivaroxaban, and 131 were receiving apixaban. Blood was taken at trough and peak within the first month (15–25 days) of treatment. PT, APTT, diluted thrombin time (dTT) calibrated for dabigatran and anti‐FXa calibrated for rivaroxaban or apixaban were determined. Results: For dabigatran, the correlation between APTT and dTT ranged from r = 0.80 to r = 0.62. For rivaroxaban, the correlation between the anti‐FXa assay and PT ranged from r = 0.91 to r = 0.73. For apixaban, the correlation between the anti‐FXa assay and PT was lower than for the two other drugs ( r = 0.81 to r = 0.54). Despite the above significant correlations, the responsiveness of PT or APTT was relatively poor. A discrepancy between global testing and DOAC plasma concentrations was shown in a considerable proportion of patients, depending on the platform and drug, with values ranging from 6% to 62%. Conclusions: Overall, poor responsiveness of the screening tests to DOAC concentrations was observed. PT and APTT normal values cannot exclude DOAC anticoagulant activity, and PT or APTT prolongation is not always associated with DOAC anticoagulant effect as determined with specific tests.